PROGRAM EVALUATION TOWARD MILLENNIUM DEVELOPMENT GOALS IN EDUCATION ASPECT AT KUNINGAN REGENCY WEST JAVA - Iman Subasman (lppm Universitas Negeri Jakarta, 2015)
The purpose of this evaluation is to find out the effectiveness of implementing the Millennium Development Goals (MDGs) in education aspect at Kuningan Regency, West Java. Evaluation models that is used are Context, Input, Process and Product (CIPP). Data were obtained through interviews, questionnaires and documents. The results of the evaluation on the aspects: (1) context, local governments follow up with local policies, (2) inputs, the implementation of the guidelines does not have a strong force of law, (3) process, increasing the access to school for the people's, and (4) product, increasing enrollment in primary education. Increasing effectiveness can be done with a stronger regional policies, monitoring, coordination of bureaucratic structure, socializing the concept of MDGs to executor and developing people perception on education.